Characterization of Maize Hybrids (Zea mays L.) for Salt Tolerance at Seedling Stage: Salt Tolerance at Seedling Stage - Ali, Muhammad; Abbasi, Ghulam Hassan; Jamil, Moazzam; Raza, Muhammad Aown Sammar; Ahmad, Salman (Biological Sciences - PJSIR, 2021)
Salinity is the most atrocious environmental aspects restricting the productivity of agricultural crops. To fulfill global increasing demand of food, selection of salt tolerant genotypes to get production from salt affected soils is imperative. In the present experiment, ten maize genotypes were evaluated against four salinity levels (control, 40 mM, 80 mM and 120 mM NaCl) using different agronomic and physiological criteria. Significant variations were observed in all morpho-physiological and ionic attributes in all maize hybrids. Results depicts that maize hybrid 2225 exhibited salt tolerance and show higher plant biomass, chlorophyll and water contents, membrane stability along with K+/Na+ ratio. While maize hybrid 8711 had lower plant growth among all maize hybrids and considered as salt sensitive genotype. The results can be used as a selection tool for salinity tolerance in maize and provide a better source for breeders for further assessment on saline lands.